COMPARISONS BETWEEN NATIONAL RURAL DEVELOPMENT PROGRAMMES OF ROMANIA – BULGARIA - Mihai, Dinu (Economics of Agriculture, 2012)
In this article is a brief analysis between the National Programmes for Rural Development of Romania and Bulgaria. In introduction are presented some aspects of rural development policy of the European Union, its importance, why is necessary such a common rural policy. The following is a brief statement of the rural development problems that exist in Romania, Bulgaria and then illustrated some similarities and differences between rural development programs of both countries. The article ends with some conclusions on this issue.